General Characteristics of Local Lore Documental Network Resources of the Libraries of Azerbaijan (Based on library collection) - Ismayilov, Nadir; Khalafova, Sevda (Technium Social Sciences Journal, 2022)
Changing economic conditions, along with the economic development of seperate parts of a country put forward the solution of territorial problems. Therefore, economic zoning as a classic direction of socio-economic geography is becaming current. Azerbaijan has a rich experience in conducting research on scientific and economic zoning. As a result of the accumulation of theoretical basis and experience in carrying out this type of work, there has been a change in the structure of economic zoning: from defining it as a natural-historical whole formation to a territorial production complex, as a non-productive sphere and management, as a socio-economic system based on the territorial unity of people, etc. Consideration of the economic region as a territorial system implies a development in which its individual subsystems and elements have factors and consequences in accordance with their internal laws. Economic regions are considered to be complex, hierarchically regulated open systems. They consist of an interconnected combination of multilevel functional and structural subsystems. Here the system and the complex relations are combined for the purpose of general development. Therefore, when studying these territorial entities, it is necessary to use a system-structural approach and take into account the accumulated experience of the complex approach used in economic zoning. At the end of this practice, rich information resources on economic regions are formed, which form the composition of local lore sources. The general issues mentioned in the article are explained in a comprehensive way.